Practical actions for fostering cross-disciplinary global health research: lessons from a narrative literature review - Justin Pulford; Yan Ding; Imelda Bates (BMJ Global Health)
Introduction Global health research involves disciplines within and beyond the health sciences. A cross-disciplinary collaborative research approach enables an interchange of knowledge and experience and stimulates innovative responses to complex health challenges. However, there is little robust evidence to guide the design and implementation of cross-disciplinary research in global health, hampering effective collective action. This review synthesised evidence on practical actions for fostering cross-disciplinary research to provide guidance on the design and implementation of research in global health.Methods We searched five electronic databases using key words. The search included original research and research notes articles in English. We used a framework adapted from the socio-ecological model and thematic synthesis for data analysis.Results Thirty-six original research and 27 research notes articles were included in the review. These were predominantly from high-income countries and indicated that practical actions on fostering cross-disciplinary research are closely linked to leadership and teamwork which should be planned and implemented at research team and institutional levels. The publications also indicated that individual qualities such as being receptive to new ideas and funders’ power and influence have practical implications for conducting cross-disciplinary research. Practical actions that individuals, research team leaders, academic institutions and funders can undertake to foster cross-disciplinary research were identified.Conclusion Our review found evidence from high-income countries, not low-and-middle-income countries, about practices that can improve cross-disciplinary research in global health. Critical knowledge gaps exist around how leadership and teamwork processes can better integrate expertise from different disciplines to make cross-disciplinary research more effective.